Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1155/2017/4835189
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Dysbiosis and Rheumatoid Arthritis: A Link between Gut Microbiota and the Pathogenesis of Rheumatoid Arthritis

Abstract: Characterization and understanding of gut microbiota has recently increased representing a wide research field, especially in autoimmune diseases. Gut microbiota is the major source of microbes which might exert beneficial as well as pathogenic effects on human health. Intestinal microbiome's role as mediator of inflammation has only recently emerged. Microbiota has been observed to differ in subjects with early rheumatoid arthritis compared to controls, and this finding has commanded this study as a possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
184
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(217 citation statements)
references
References 83 publications
(156 reference statements)
2
184
0
6
Order By: Relevance
“…Gut microbiota contribute to the pathogenesis of RA by disruption of the innate and adaptive immune system through induction of self‐protein citrullination in immune cells, such as neutrophils and production of inflammatory cytokines and autoantibodies in genetically susceptible individuals . A link between gut microbiota and the pathogenesis of RA has been further reviewed by Horta‐Baas et al…”
Section: Ra Triggers and Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Gut microbiota contribute to the pathogenesis of RA by disruption of the innate and adaptive immune system through induction of self‐protein citrullination in immune cells, such as neutrophils and production of inflammatory cytokines and autoantibodies in genetically susceptible individuals . A link between gut microbiota and the pathogenesis of RA has been further reviewed by Horta‐Baas et al…”
Section: Ra Triggers and Pathogenesismentioning
confidence: 99%
“…17 Gut microbiota contribute to the pathogenesis of RA by disruption of the innate and adaptive immune system through induction of selfprotein citrullination in immune cells, such as neutrophils and production of inflammatory cytokines and autoantibodies in genetically susceptible individuals. 25 A link between gut microbiota and the pathogenesis of RA has been further reviewed by Horta-Baas et al 27 There are several checkpoints and mechanisms contribute to the control of escaping autoreactive T-and B-cells. These mechanisms include the inhibitory membrane molecules, receptor editing and apoptosis early in ontogeny, followed by energy induction before or immediately after emigration from the thymus or bone marrow to the periphery.…”
mentioning
confidence: 99%
“…The intestinal microbiota in RA is characterized by an expansion and/or decrease of bacterial groups as compared to controls, supporting that gut dysbiosis is likely relevant for RA pathogenesis . Not surprisingly, however, the microbiome in RA has some variations depending on the patient’s origin and ethnicity , which supports the notion that the aetiology of RA cannot be explained by single pathogen or risk factor. In RA patients from North America, 16S and shotgun sequencing on stool samples initially identified that Prevotella copri ( P. copri ) strongly correlates with disease in new‐onset untreated RA .…”
Section: Phase 2: Preclinical Ramentioning
confidence: 79%
“…The overexpression of FLNA has been identified to be related to several malignancies, such as the lung cancer, melanoma, and breast cancer . Interestingly, FLNA has been described as one of the proteins from common gut bacteria that could evoke the immune response in rheumatoid arthritis patients with no health functions . Bin1 protein was another important DP related to the immune system, especially the Fc gamma R‐mediated phagocytosis.…”
Section: Discussionmentioning
confidence: 99%